Description of the male of Rediviva steineri Kuhlmann, 2012 (Hymenoptera: Melittidae), an endemic oil-collecting bee species from South Africa - Melin, Annalie; Colville, Jonathan F. (African Entomology, 2022)
We describe the male of Rediviva steineri Kuhlmann, 2012; distinguished by the shape and the margin of the apical plate of the eighth sterna and the vestiture of metasomal terga two and three. Five males were collected at the type locality of the female (Farm Doornbosch, Western Cape, South Africa). We examined the types of three other closely related species (R. pallidula, R. brunnea and R. whiteheadi) and provide images of the eighth sterna for comparison with R. steineri and update Whitehead et al.’s (2008) identification key for the males of these species.